Thermodynamics and Kinetics of Reaction Between NaCl and KF - Yang, Hai-Li; Wang, Xin-Yue; Tang, Guo-Zhang; Zhang, Yu-Zhu; Li, Yun-Gang (Asian Journal of Chemistry, 2014)
Thermodynamics and kinetics of reaction between NaCl and KF were investigated. The negative Gibbs free energy change for the reaction indicated that the reaction was thermodynamically possible. Differential thermal analysis was used to study the reaction. Differential thermal analysis analysis revealed that the reaction between NaCl and KF occurred at 595 °C after a eutectic liquid formation at 582 °C and its activation energy was calculated to be 805 KJ/mol using Kissinger differential method. Moreover, powder X-ray diffraction measurement further confirmed the formation of NaF and KCl.